Estimation of candidate genes in the development of a combination of endometrial hyperplasia and uterine fi broids - Irina V. Ponomarenko; Mikhail I. Churnosov (Медицинский вестник Юга России, 2017)
Objective: the study of bioinformatics by six genetic polymorphisms (rs1782507, rs555621, rs7753051, rs887912, rs6732220, rs4986938) in the formation of a combination of endometrial hyperplasia with uterine myoma in women in the Central region of Russia. Materials and methods: the study group consisted of 1151 employees, including 170 patients with a combination of uterine fi broids with endometrial hyperplastic processes and 981 women in the control group without proliferative diseases of the pelvic organs. Material for the study were DNA samples isolated from venous blood by phenol-chloroform extraction.Analysis of the investigated polymorphisms was carried out by the detection ATK-man probes using real-time PCR. Results: risk factors for the development of a combination of endometrial hyperplasia and uterine fi broids combination of molecular genetic markers with rs673220, and rs4986938 and G rs887912 (ОR = 1.70), with rs6732220 and rs555621, g rs887912 (ОR = 1.53) and C rs1782507 T rs7753051 and rs887912 G (ОR = 1.40). Conclusion: the obtained data testify to the signifi cant contribution of combinations of polymorphic variants rs1782507, rs555621, rs7753051, rs887912, rs6732220 and rs4986938 to the formation of a combination of endometrial hyperplasia and uterine fi broids among women in the Central region of Russia.